2010
DOI: 10.3389/fnsys.2010.00150
|View full text |Cite
|
Sign up to set email alerts
|

Influences of neural pathway integrity on children’s response to reading instruction

Abstract: As the education field moves toward using responsiveness to intervention to identify students with disabilities, an important question is the degree to which this classification can be connected to a student's neurobiological characteristics. A few functional neuroimaging studies have reported a relationship between activation and response to instruction; however, whether a similar correlation exists with white matter (WM) is not clear. To investigate this issue, we acquired high angular resolution diffusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Given the lack of previous studies in dyslexia examining potential thalamic connectivity differences, our hypotheses were necessarily general; however, given the differences in functional activation in the thalamus between typically developing and dyslexic groups, we expected that we would find differences in thalamo-cortical connectivity between the TD and DYS groups. While specificity of these regions was difficult to pinpoint, in the one previous diffusion tractography-based connectivity study (Davis et al, 2010), we showed differences in thalamo-cortical connectivity between responders and nonresponders to reading intervention. Therefore, we expected thalamo-cortical differences between groups in the standard language-related regions near the perisylvian cortex, such as the occipito-temporal cortex (OTC) and the temporo-parietal cortex (TPC).…”
Section: Introductionmentioning
confidence: 45%
See 1 more Smart Citation
“…Given the lack of previous studies in dyslexia examining potential thalamic connectivity differences, our hypotheses were necessarily general; however, given the differences in functional activation in the thalamus between typically developing and dyslexic groups, we expected that we would find differences in thalamo-cortical connectivity between the TD and DYS groups. While specificity of these regions was difficult to pinpoint, in the one previous diffusion tractography-based connectivity study (Davis et al, 2010), we showed differences in thalamo-cortical connectivity between responders and nonresponders to reading intervention. Therefore, we expected thalamo-cortical differences between groups in the standard language-related regions near the perisylvian cortex, such as the occipito-temporal cortex (OTC) and the temporo-parietal cortex (TPC).…”
Section: Introductionmentioning
confidence: 45%
“…In addition to the voxel-based morphometry analyses that focus on the localized white matter microstructural properties, diffusion tractography was employed to map the white matter fiber pathways which are important for reading, including arcuate fasciculus, corpus callosum, inferior longitudinal fasciculus, and inferior frontal occipital fasciculus (Catani et al, 2005;Odegard et al, 2009;Rauschecker et al, 2009;Saygin et al, 2013;Yeatman et al, 2012) (for a review, see Vandermosten et al, 2012;Wandell, 2011). Brain connectivity between distant regions, such as thalamus, angular gyrus, superior temporal cortex, and insula, has been shown to be related to reading ability in children (Davis et al, 2010). These findings suggest that the characteristics of white matter pathways between distant cortical regions are potentially an important aspect of the neurobiology of dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found increased connectivity between the thalamus and both the lateral prefrontal cortex and the sensorimotor cortex in English-speaking dyslexic children ( Fan et al, 2014 ). Furthermore, Fan et al (2014) observed a negative correlation between thalamo-cortical connectivity and a composite score of visual word identification and word attack measures, while another study found a negative correlation between thalamo-cortical connections and pseudoword reading ( Davis et al, 2010 ). Contrary to the increased anterior thalamo-cortical connectivity, more posterior thalamo-cortical connectivity, i.e., between LGN and V5/MT may be reduced in dyslexia ( Müller-Axt et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One application is to use neuroimaging measurements to predict the likelihood of success of specific interventions. For example, EEG potentials (Maurer et al 2009, Molfese 2000) and MR measures (Davis et al 2010; Hoeft et al 2007, 2011) have been used to predict reading outcomes. Such measures can be used to select the best intervention for an individual (Gabrieli 2009).…”
Section: Dyslexiamentioning
confidence: 99%